DISEASES THAT MAY OCCUR AS A RESULT OF FACTORS AFFECTING THE HIGHER NERVOUS SYSTEM - Scientific Supervisor: Nurimova Dilorom Majidovna; Uraimjanova Ruxshonabonu Ilxomjon qizi (Journals Park Publishing, 2024)
In this article, the formation of the higher nervous system, scientific views on it and the factors affecting the higher nervous system, as well as diseases arising from it, as well as scientific views on their prevention, are highlighted.
Keywords: people, higher nervous system, disease symptoms, epilepsy, migraine, etiopathogenesis, epidemiology, clinic, arachnoiditis, arachnoiditis, arachncephalon and deuterencephalon.